(untitled) (Journal of Nepal Physical Society, 2021)
In muon spin rotation and relaxation (μSR) method, time evolution of muon spin polarization provides the information about local electronic and spin dynamic states of the material. Quantum simulation and estimated frequency of calculated the spectra help to interpret the observed polarization spectra. Based on spin dipole interaction between the muon and nearby nuclei (14N, 15N and proton) in zero field measurement case, muon spin polarization spectra and corresponding frequencies are estimated using the quantum simulation. The oscillation frequency increases with approaching the muon towards the nuclei. Variation of separation between frequency positions with changing distance between muon and nuclei indicates the distribution of the magnetic field at the muon site. This study will help to distinguish the origin of oscillation in zero field μSR spectra in the isolated system containing 14N and 15N nuclei (e.g., glycine with 14N, glycine with 15N).